Comparação da eficiência de intrusão de primeiros molares superiores com correção ortodôntica de acordo com dois protocolos: ancoragem em dois e três mini- implantes. - Paccini, Juliana Volpato Curi (2012)
The aim of the present study was to investigate the dentoalveolar and skeletal cephalometric changes produced by the intrusion of maxillary first molars through mini-implant for orthodontic anchorage. Nineteen patients with a total of 25 extruded upper first molars were selected and managed with mini-implants combined with orthodontic treatment. The patients were divided into two groups concerning the number of mini-implants used: Group 1 was formed by 15 first molars intruded by two mini-implants, while Group 2 was formed by 10 first molars intruded by three mini-implants. The dentoalveolar and skeletal cephalometric changes was evaluated by lateral cephalometric analysis performed at the beginning (T1) and after the intrusion of the teeth (T2). According to the results, both protocols were effective for the intrusion of maxillary first molars, with no significant differences between them. Considering the skeletal changes, there was a significant decrease in FMA values between the start and end of the trial, indicating a counter-clockwise rotation of the mandible. It was concluded that the intrusion of extruded maxillary first molars through mini-implant for orthodontic anchorage has an efficient orthodontic mechanics, with no significant differences between the protocols evaluated.